A comparison of friction behaviour for ex vivo human, tissue engineered and synthetic skin. (November 2016) - Bostan, L.E.; Taylor, Z.A.; Carré, M.J.; MacNeil, S.; Franklin, S.E.; Lewis, R.
Abstract: Skin tribology is complex and in situ behaviour of skin varies considerably between test subjects. The main influencing factor, elasticity, varies due to structural and moisture differences. To find a more reliable test platform, for the first time, synthetic and biological (tissue engineered) substitutes were compared to ex vivo skin, epidermis and dermis. Friction initially increased with rising hydration, before decreasing beyond a threshold for all samples. Friction for Synthetic skin and dermis increased at a similar rate to the other samples, but from a different starting point, and friction dropped at lower hydration. Tissue engineered skin could provide a reliable test platform, but the synthetic skin could only be used if the offset in the data is accounted for. Highlights: ● Comparison of friction behaviour between ex-vivo skin and synthetic and biological substitutes. ● First tribological testing of tissue engineered skin. ● New knowledge of moisture effects established and assessment of synthetic skin viability as a skin test platform.